Gestational folic acid content alters the development and function of hypothalamic food intake regulating neurons in Wistar rat offspring post-weaning. (1st February 2020) - Yang, Neil Victor; Pannia, Emanuela; Chatterjee, Diptendu; Kubant, Ruslan; Ho, Mandy; Hammoud, Rola; Pausova, Zdenka; Anderson, G. Harvey
Abstract : Background : Folic acid plays an important role in early brain development of offspring, including proliferation and differentiation of neural stem cells known to impact the function of food intake regulatory pathways. Excess (10-fold) intakes of folic acid in the gestational diet have been linked to increased food intake and obesity in male rat offspring post-weaning. Objective : The present study examined the effects of folic acid content in gestational diets on the development and function of two hypothalamic neuronal populations, neuropeptide Y (NPY) and pro-opiomelanocortin (POMC), within food intake regulatory pathways of male Wistar rat offspring at birth and post-weaning. Results : Folic acid fed at 5.0-fold above recommended levels (5RF) to Wistar dams during pregnancy increased the number of mature NPY-positive neurons in the hypothalamus of male offspring, compared to control (RF), 0RF, 2.5RF, and 10RF at birth. Folic acid content had no effect on expression and maturation of POMC-positive neurons. Body weight and food intake were higher in all treatment groups (2.5-, 5.0-, and 10.0-fold folic acid) from birth to 9 weeks post-weaning compared to control. Increased body weight and food intake at 9-weeks post-weaning were accompanied by a reduced activation of POMC neurons in the arcuate nucleus (ARC). Conclusion : Gestational folic acid content modulates expression of mature hypothalamic NPY-positive neurons at birth and activation of POMC-positive neurons at 9-weeks post-weaning in the ARC of male Wistar rat offspring which may contribute to higher body weight and food intake later in life.